2012
DOI: 10.1093/carcin/bgr317
|View full text |Cite
|
Sign up to set email alerts
|

Repression of mammosphere formation of human breast cancer cells by soy isoflavone genistein and blueberry polyphenolic acids suggests diet-mediated targeting of cancer stem-like/progenitor cells

Abstract: Mammary stem cells are undifferentiated epithelial cells, which initiate mammary tumors and render them resistant to anticancer therapies, when deregulated. Diets rich in fruits and vegetables are implicated in breast cancer risk reduction, yet underlying mechanisms are poorly understood. Here, we addressed whether dietary factors selectively target mammary epithelial cells that display stem-like/progenitor subpopulations with previously recognized tumor-initiating potential. Using estrogen receptor-positive M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
91
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 49 publications
8
91
0
Order By: Relevance
“…Moreover, in a mouse model of breast cancer and in breast cancer cells in vitro, dietary intake of soy protein isolate and treatment with Gen, respectively, decreased the frequency of the mammary basal stem celllike subpopulation, which was associated with decreased mammary tumor incidence and oncogenic molecular profile (Montales et al 2012;Rahal et al 2013). Based on this previous body of work, we hypothesized that combination(s) of MET and bioactive soy factors would increase the therapeutic efficacy of the CRC drug 5-FU by targeting cancer stem cells.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Moreover, in a mouse model of breast cancer and in breast cancer cells in vitro, dietary intake of soy protein isolate and treatment with Gen, respectively, decreased the frequency of the mammary basal stem celllike subpopulation, which was associated with decreased mammary tumor incidence and oncogenic molecular profile (Montales et al 2012;Rahal et al 2013). Based on this previous body of work, we hypothesized that combination(s) of MET and bioactive soy factors would increase the therapeutic efficacy of the CRC drug 5-FU by targeting cancer stem cells.…”
Section: Discussionmentioning
confidence: 96%
“…CD44 ? cell fractions were seeded at a density of 2 9 10 3 cells per well in ultra-low attachment plates (Corning Inc., Corning, NY) in plating medium [phenol red-free MEM supplemented with B27 media (Invitrogen); 20 ng/ml human basic fibroblast growth factor (Invitrogen, Carlsbad, CA), 20 ng/ml epidermal growth factor (Invitrogen), 10 lg/ml heparin (Sigma-Aldrich), 1 % ABAM, and 100 lg/ml gentamicin (Sigma-Aldrich)] (Montales et al 2012). Treatments were MET (60 lM), soy bioactive factors (3 lM each for b-con and Gly; 2 lM each for Lun and Gen), and insulin (2 lM), singly and with the indicated combinations.…”
Section: Colonosphere Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro studies of the effect of soy isoflavones on breast cancer cell lines reported some beneficial effects such as reactivation of tumor suppressor genes BRCA1 and BRCA2 silenced by promoter hypermethylation (Bosviel et al, 2012), inhibition of the breast cancer progenitor cell proliferation (Montales et al, 2012), induction of apoptosis and inhibiting the proliferative signals mediated through NFκB (Seo et al, 2011). Conversely, some others have noticed opposite, stimulatory, effects on tumor cell growth (van Duursen et al, 2011).…”
Section: Phytoestrogensmentioning
confidence: 99%